Exploring Undergraduate EFL Students’ Comprehension of Conversational Implicatures - Ardi Nugroho; Jessica Gloria Antouw (Universitas Negeri Medan, 2023)
Pragmatic competence is crucial for language learners, more specifically EFL learners. Nonetheless, it has been found that when it comes to English language teaching in the EFL context, more emphasis is put on linguistic instead of pragmatic competence. Furthermore, in terms of understanding conversational implicatures, little attempt has been made in the EFL classrooms to make the learners aware of the use of implicature as a communication tool. From this, the writers have become interested in exploring undergraduate EFL students’ ability to comprehend conversational implicatures, more specifically, students from the English Department at Bunda Mulia University, Jakarta. Additionally, the writers would like to investigate whether the students’ English proficiency influence their ability to understand the implied meaning behind conversational implicatures. A total of 60 students are included as the respondents. For the data collection, the researchers distribute a multiple-choice test to the respondents, and they are also asked to do the online English proficiency test. The result of the multiple-choice test is analyzed qualitatively to find out which of the four types of implicatures are the most problematic for the students. Additionally, the result of these two tests is then analyzed quantitatively using the Pearson Product Moment Correlation to find out whether there is a significant relationship between these two variables. The result shows that students had the most problem understanding indirect refusals, and that there is a significant positive correlation between the learners’ English proficiency and their ability to understand the indirect meanings in the conversational implicatures.